1900 Md. Laws 143-44 - (:unkn) unknown (My University, 1900)
§ 13: And be it enacted, That the Commissioners shall have the power, by ordinances duly enacted . . . to regulate or prevent the firing of cannon, guns, pistols, squibs, or any kind of firearms or explosives...
Keywords: DISCHARGE